A prospective study of post-operative complications and its management following open hemorrhoidectomy in a tertiary care hospital - Amalesh Barman; Niharika Lama; Sisir Das; Dibyajit Datta (Asian Journal of Medical Sciences, 2024)
Background: Surgery is the most effective treatment for hemorrhoids and is particularly recommended for prolapsing piles during defecation that may be reduced manually (Grade III) and irreducible hemorrhoids (Grade IV). Numerous methods have been proposed for surgical therapy, and most have similar success rates. But serious post-operative complications are rarer in open technique than stapled hemorrhoidopexy. Prompt identification of post-operative complications is necessary to avoid significant patient morbidity.